2021
DOI: 10.1155/2021/8894685
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Overexpression of GDF5 in Adipocytes but Not Hepatocytes Alleviates High-Fat Diet-Induced Nonalcoholic Fatty Liver in Mice

Abstract: Objective. Our recent study demonstrated that growth differentiation factor 5 (GDF5) could promote white adipose tissue thermogenesis and alleviate high-fat diet- (HFD-) induced obesity in fatty acid-binding protein 4- (Fabp4-) GDF5 transgenic mice (TG). Here, we further investigated the effects of systemic overexpression of the GDF5 gene in adipocytes HFD-induced nonalcoholic fatty liver disease (NAFLD). Methods. Fabp4-GDF5 TG mice were administered an HFD feeding. NAFLD-related indicators associated with lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…BMP14, also known as growth differentiating factor 5 (GDF5), has so far mostly been studied in the context of cartilage and bone formation and homeostasis [7]. To date, only one study analyzed BMP14 in the context of chronic liver disease and found that the systemic overexpression of BMP14 in adipose tissues reduced high-fat diet-induced fatty liver disease in mice [8]. In addition, only a few studies exist regarding BMP14 and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…BMP14, also known as growth differentiating factor 5 (GDF5), has so far mostly been studied in the context of cartilage and bone formation and homeostasis [7]. To date, only one study analyzed BMP14 in the context of chronic liver disease and found that the systemic overexpression of BMP14 in adipose tissues reduced high-fat diet-induced fatty liver disease in mice [8]. In addition, only a few studies exist regarding BMP14 and cancer.…”
Section: Introductionmentioning
confidence: 99%